Identification and phylogenetic inference in different mollucs nudibranch species via mitochondrial 16S rDNA - Alqudah, Ali; Saad, Shahbudin; Nordin, Noor Faizul Hadry; Darnis, Deny Susanti (Rede Brasileira de Informações Biológicas - Rebibio, 2015)
The molecular analysis of marine life is an essential approach to discover new classes of natural products and to improve the management and sustainable utilization of these useful genetic resources. Mitochondrial DNA markers are frequently utilized to identify any organism up to the species level. This study provides insight into the significant role of species discrimination based on 16S rDNA, and this method could be a powerful tool for the identification of animal species. 16S rDNA sequences of each studied species (Phyllidia varicosa (Lamarck, 1801) and Phyllidiella pustulosa (Cuvier, 1804)) from two locations in the coastal waters of Balok in Pahang State and Bidong Island in Terengganu State were aligned to identify the phylogenetic relationships among them. The phylogenetic tree produced in this study is consistent with those previously presented in the literature. The divergence of sequences was adequate to identify the samples at the species level with the assistance of the GenBank database and the BLAST tool. The results presented here provide useful information for a better understanding of this marine genetic resource. This genetic approach could simplify the identification of the species accurately for further analysis.